Comparison of Starch from Locally Grown Food Crops as a Pharmaceutical Excipient: A Systematic Review - Reagan, Kikweranono Ronald; Jonans, Tusiimire (African Journal of Pharmaceutical Sciences, 2024)
Starch is a widely used material with various applications in many starch based industries like pharmaceuticals, food and textiles, breweries and distillers due to its adhesive, gelling, thickening, swelling and film forming properties, making it to be used as a binder and disintegrant in pharmaceutical industries, but as a country becomes more industrialized, demand for both native and modified starches increases but these demands are currently being somewhat met through imports instead of locally made starch yet the sources of the starches are Maize, Cassava, Irish potato among others, so this review evaluated the available evidence on use of maize, cassava, and potatoes as sources of pharmaceutical grade starch in order to comprehensively prove with evident the possibility of their application and identify the best option by properties respectively using Articles containing Starch from these sources used as Pharmaceutical and conclusively, there was a strong evidence that all the sources produced starch which met the pharmacopeial grade standard and maize having the highest yield.
Keywords: Starch; Pharmaceutical; Excipient; Binder; Disintegrant; Pharmacopeia